PENGEMBANGAN E-MODUL IPAS BERMUATAN PROJECT BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Tri Nurahmania, Tri Nurahmania; Nurwalidainismawati; Yeni Wardatunnissa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking is one of the essential 21st-century skills and is a key focus of the Independent Curriculum. However, preliminary analysis at SDN Inpres Leu indicates that students' critical thinking skills are still low due to the dominance of lecture methods and the lack of use of interactive digital media. This study aims to develop a valid, practical, and effective Science (IPAS) e-module containing Project Based Learning (PJBL) to improve elementary school students' critical thinking skills. The study used the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, fifth-grade teachers, and 17 fifth-grade students at SDN Inpres Leu. Data were collected through validation sheets, teacher and student response questionnaires, and critical thinking skills tests based on the Facione indicator. The validation results showed that the material aspect scored 97.5% and the media aspect reached 90%, both of which are categorized as very valid. Teacher and student responses showed a practicality score of 95%, categorized as very practical. The effectiveness test using the N-gain calculation yielded a score of 0.74, categorized as high, indicating a significant improvement in students' critical thinking skills. In conclusion, the developed Science and Technology e-module with PJBL content was deemed feasible, practical, and effective as an innovative learning medium to support the implementation of the Independent Curriculum.